Vibration suppression of tunnel boring machines using non-resonance approach. (November 2020) - Yang, Bo; Chen, Shumei; Sun, Shuaishuai; Deng, Lei; Li, Ziqi; Li, Weihua; Li, He
Highlights: A non-resonance method using MRE isolator is proposed to suppress TBM's vibration. The resonance of the TBM can be avoided by controlling its natural frequency. The improved vibration control performance of the TBM with MRE isolator is verified. Abstract: Tunnel boring machines (TBM) are efficient tunnel excavation equipment, and the number of TBM in many countries is increasing rapidly. TBM works in a harsh geological environment and long-term vibration will cause tremendous damages, including loosening the pipeline and damaging the mechanical system on the main frame of TBM. In this paper, a variable stiffness magnetorheological elastomer (MRE) isolator is installed under the main frame in order to control its resonance frequency to avoid the vibration resonance to reduce the high-level vibration of TBM, this is called non-resonance control approach. A multi-degree-of-freedom dynamics model of the TBM is established as the first step. The performance of the MRE isolator on vibration control of TBM is numerically evaluated. Then a scaled TBM is built for experimental evaluation and a laminated MRE isolator is designed, prototyped according to the requirement of the scaled TBM; its properties are tested by a shaking table, including its current-dependency, frequency-dependency, and amplitude-dependency features. In the end, the MRE is installed on the scaled TBM platform to evaluate its vibration reduction effectiveness. The experimental test results demonstrate that the displacement amplitude of the TBM vibration could be reduced by up to 20.18% and 14.52% under harmonic sweep excitation and nonsynchronous excitation, respectively.